Building an Extensive Experience in Video Games and Movies, a Transmedia Storytelling - Octavianus Frans; Jonata Witabora (Bina Nusantara University, 2017)
Transforming video games into movies and transforming movies into video games has been a common thing nowadays. With advanced technology, what can be done in a video game can also be done in a movie, and vice versa. Good attention to details is important in a transformation process as the final product has to be as good as the original one, if not better. To be able to do well in transforming an art form to another, it is important to understand the whole process and how it was first done.Â